2022
DOI: 10.1364/ao.458463
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency InGaN blue LEDs with reduced positive sheet polarization

Abstract: The formation of positive sheet polarization charges at the interface of the last quantum barrier (QB) and the conventional p -type electron-blocking layer (EBL) creates significant band bending, leading to severe electron leakage and poor hole injection in III-nitride light-emitting diodes. We report that the positive sheet polarization charges are mitigated by employing a lattice matched AlGaN last QB. Electron leakage is dramatically reduced due to the increased effective conduction band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Velpula et al [148] indicated that the main reasons for the efficiency droop in LEDs are a large overflow of electrons from the active region into the active region and insufficient hole injection into the active region. Previous studies addressed this problem by introducing p-type AlGaN as an electron-blocking layer (EBL) to prevent electron leakage [42,149].…”
Section: The Role Of the Electron-blocking Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Velpula et al [148] indicated that the main reasons for the efficiency droop in LEDs are a large overflow of electrons from the active region into the active region and insufficient hole injection into the active region. Previous studies addressed this problem by introducing p-type AlGaN as an electron-blocking layer (EBL) to prevent electron leakage [42,149].…”
Section: The Role Of the Electron-blocking Layermentioning
confidence: 99%
“…Moreover, the majority of charge carriers are likely confined and undergo radioactive recombination in the last quantum well just prior to the last QB (quantum barrier) of III-nitride-based multi-QW LEDs [154]. Velpula et al [148] utilized a novel AlGaN QB as a lattice-matched EBL used instead of a conventional GaN QB. The positive sheet charges at the last QB/EBL can be eliminated due to lattice-matched conditions at this interface.…”
Section: The Role Of the Electron-blocking Layermentioning
confidence: 99%
“…Nanostructured III-nitride materials have attracted significant attention due to their great potential applications in micro-displays, conformable light sources, and augment/virtual reality technology. The light-emitting diodes (LEDs) that could emit different wavelengths from ultraviolet (UV), visible light, and infrared (IR) by controlling the In, Ga, and Al composition in In­(Al)­GaN materials are intensively investigated. However, the fabrication of high-efficiency full-color LEDs, especially at long wavelengths (green and red light), remains a challenge that hinders the commercial availability of micro-displays. In addition, luminous efficacy of the LEDs can attain 50 to 70% of the theoretical maximum . More than 30% of the energy is converted into heat which reduces the LED luminescent efficacy and lifetime.…”
Section: Introductionmentioning
confidence: 99%